Identification of individual neurons reflecting short- and long-term visual memory in an arthropod - Tomsic, D. (2003)
Ideally, learning-related changes should be investigated while they occur in vivo, but physical accessibility and stability limit intracellular studies. Experiments with insects and crabs demonstrate their remarkable capacity to learn and memorize visual features. However, the location and physiology of individual neurons underlying these processes is unknown. A recently developed crab preparation allows stable intracellular recordings from the optic ganglia to be performed in the intact animal during learning. In the crab Chasmagnathus, a visual danger stimulus (VDS) elicits animal escape, which declines after a few stimulus presentations. The long-lasting retention of this decrement is mediated by an association between contextual cues of the training site and the VDS, therefore, called context-signal memory (CSM). CSM is achieved only by spaced training. Massed training, on the contrary, produces a decline of the escape response that is short lasting and, because it is context independent, is called signal memory (SM). Here, we show that movement detector neurons (MDNs) from the lobula (third optic ganglion) of the crab modify their response to the VDS during visual learning. These modifications strikingly correlate with the rate of acquisition and with the duration of retention of both CSM and SM. Long-term CSM is detectable from the response of the neuron 1 d after training. In contrast to MDNs, identified neurons from the medulla (second optic ganglion) show no changes. Our results indicate that visual memory in the crab, and possibly other arthropods, including insects, is accounted for by functional changes occurring in neurons originating in the optic lobes.